Letter (copy) : Spanish Fund - Parkin, E. G.
028-0203-001 EP/EK/482. Finance. 4th September, 1936. Mr. H. V. Tewson, The Royal Hotel, Plymouth, Devon. Dear Mr. Tewson, SPANISH FUND. The following is the statement of subscriptions received to date in connection with the Spanish appeal: £. s. d. General Council 1,000.0.0. Trade Unions 7,532.8.0. Trades Councils and Labour Parties 1,145.11.7. Individual and other Subscriptions 3,189.14.9 Total Subscriptions received from British Sources 12,867.14. 4. Remittances from America 6,954.5.9. Total £19,822.0.1. Yours sincerely, 292/946/28/203